2015
DOI: 10.1002/2015gl063989
|View full text |Cite
|
Sign up to set email alerts
|

D″ discontinuity structure beneath the North Atlantic from Scd observations

Abstract: We analyzed transverse and radial component recordings from the 2010 M6.3 southern Spain earthquake (depth = 620 km) recorded on 370 broadband stations in North America. We grouped these seismograms into subarrays and applied fourth root vespa processing (vespagram analysis) in order to enhance low‐amplitude arrivals. These vespagrams show clear Scd arrivals which indicate the existence of the D″ discontinuity beneath the North Atlantic Ocean (45–60°N, 45–55°W). These observations are best fit with a +2–4% vel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
21
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 30 publications
8
21
0
Order By: Relevance
“…These velocity jumps range from 0.48% (in mod7) to 2.52% (in mod11). The strength of these velocity discontinuities is similar to that reported for downwelling regions (e.g., Helmberger et al, 2005; Sun et al, 2016; Yao et al, 2015; Young & Lay, 1987a, 1987b). …”
Section: Apparent Splitting For a Deep Earthquake Sourcesupporting
confidence: 87%
“…These velocity jumps range from 0.48% (in mod7) to 2.52% (in mod11). The strength of these velocity discontinuities is similar to that reported for downwelling regions (e.g., Helmberger et al, 2005; Sun et al, 2016; Yao et al, 2015; Young & Lay, 1987a, 1987b). …”
Section: Apparent Splitting For a Deep Earthquake Sourcesupporting
confidence: 87%
“…Nonetheless, the trade‐off between velocity and height implies that our discontinuity height in this region may be somewhat elevated as the upgoing Scd paths will be sped up in the presence of the topographic high. Midmantle seismic heterogeneity can also affect the Scd‐S differential times used in estimating discontinuity height [e.g., Yao et al ., ]. In our study region there are significant regions of midmantle high wave speeds due to the subducting Farallon slab.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we do not use differential slowness to constrain height. Previous modeling efforts have demonstrated that to match δ u S‐Scd a negative velocity gradient immediately above the D ″ discontinuity is required [ Yao et al ., ]. There is no correlation between measured amplitude ratios and discontinuity height.…”
Section: Methodsmentioning
confidence: 99%
“…In this paper, we are devoted to locate paleoslabs in D" near the Perm Anomaly. Here, we analyzed the Scd arrival—a lowermost mantle triplication occurring as the downgoing S wave refracts below the D" discontinuity (e.g., Sun et al, ; Yao et al, )—to investigate the D" discontinuity sampling the southeastern edge of the Perm Anomaly (Figure ); the Scd arrivals are recorded by a network comprising 57 stations in southeastern Europe from a deep earthquake with magnitude of Mw 6.5 that occurred on 4 September 2013 beneath the northwestern Pacific subduction zone. The event with moderate magnitude (5.8 < Mw < 7) was selected to limit the duration of source time function (Sun et al, ).…”
Section: Data Methods and Analysesmentioning
confidence: 99%